2019
DOI: 10.3390/cancers11070909
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Outcome in Patients with Pheochromocytoma and Paraganglioma Treated with 177Lu-DOTATATE

Abstract: Peptide receptor radiotherapy (PRRT) with 177Lu-DOTATATE has emerged as a promising therapy for neuroendocrine tumors (NETs). This retrospective cohort study aimed to assess the outcome of PRRT for 22 patients with histopathologically confirmed pheochromocytoma (PCC) and paraganglioma (PGL), of which two were localized and 20 metastatic. Radiological response utilized response evaluation criteria in solid tumors 1.1 and toxicity was graded according to common terminology criteria for adverse events version 4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 19 publications
0
54
0
2
Order By: Relevance
“…177 Lu-tetra-aza-cyclo-dodecanetetraacetic acid–DPhe1-Tyr3-octreotate (DOTATATE) has shown favorable efficacy in controlling symptoms and tumor progression in most of the previous studies ( 5 , 6 ). A recently published meta-analysis has reported good efficacy (disease control rate: 80% (95% CI: 77–89%)) with an encouraging safety profile ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…177 Lu-tetra-aza-cyclo-dodecanetetraacetic acid–DPhe1-Tyr3-octreotate (DOTATATE) has shown favorable efficacy in controlling symptoms and tumor progression in most of the previous studies ( 5 , 6 ). A recently published meta-analysis has reported good efficacy (disease control rate: 80% (95% CI: 77–89%)) with an encouraging safety profile ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying predictors of early response to PRRT may help with appropriate patient selection. So far, the only recognized predictor of response to PRRT in PPGL patients is the Ki-67 labeling index ( 6 ). Various studies of PRRT in neuroendocrine tumors (NET) have found baseline SUV max as an important predictor of response to PRRT ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with 68 Ga-imaging ( Figure 10 ), it represents a powerful theranostic tool for the management of neuroendocrine tumors (NETs) [ 175 ]. Current research with [ 177 Lu]-DOTATATE aims to improve the safety and efficacy of this procedure, enlarge possible indication, notably in advanced, poorly-differentiated, GEP-NETs, [ 176 , 177 ] or other NETs, such as pheomochromocytoma or paraganglioma [ 178 , 179 ].…”
Section: Targeting Of Somatostatin Receptors With Radiopharmaceutimentioning
confidence: 99%
“…In a recently published retrospective study by Vyakaranam et al,22 patients received 177 Lu-DOTATATE (n = 3 with four cycles of 7.4 GBq and n = 19 with dosimetry-guided PRRT where as many cycles (3-11) were administered until 23 Gy to the kidneys or 2 Gy to bone marrow was reached) achieving a median OS of 49.6 (range 8.2-139) months and a median PFS of 21.6 (range 6.7-138) months (Vyakaranam et al 2019). Nine of 22 patients treated were progressive at start.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…Endocrine-Related Cancer undergo both 123 I-MIBG and 68 Ga-DOTA-SSA imaging, and based on the results, the first-line therapy should be chosen (Vyakaranam et al 2019). In case of mosaic expression of the two tracers, treatment with both can be considered, and if any lesion/s lack uptake of both the tracers, then it can be targeted by additional beam radiation (Vyakaranam et al 2019). Furthermore, PRRT with combined and/or maintenance cold SSA therapy should be considered as it demonstrated superior results compared to PRRT monotherapy in NETs (Yordanova et al 2018).…”
Section: :11mentioning
confidence: 99%